Integration of cardiac rhythmogenesis levels: cardiac rhythm generator in the brain - V. M. Pokrovsky (Бюллетень сибирской медицины, 2006)
Data which were obtained last time allow to re-comprehend ideas concerning mechanisms of cardiac rhythm regeneration and demonstrate existence of rhythm generator in the central nervous system in addition to such in the heart itself. Intracardiac generator is a life-supporting factor which supports pumping function of the heart while central nervous system is in deep inhibition status. Central generator provides adaptive reactions of the heart in natural medium. Integration of the two hierarchic levels of rhythmogenesis provides reliability and functional perfection of cardiac rhythm generation system in the organism.